PEMBINAAN KARAKTER MAHASISWA BERBASIS LIVING VALUES EDUCATION - Hayati Nufus (IAIN Ambon, 2019)
ABSTRACT: This study supports providing solutions to foster student character in the Ambon IAIN environment based on the Living Values Education program. This research is a qualitative descriptive type with instruments of interview (interview) and FGD (focus group discussions), the LVE material used is the values of peace, appreciation, love, unity and divinity (religious). The subjects of this study were the third semester FITK IAIN Ambon students consisting of majors namely Islamic Education and Biology Education which were filled with 23 people and 2 lecturers from two majors. This study uses descriptive narrative analysis. The results of the study provide an overview of Life Values Education must be carried out and developed in everyday life. Whether it is a character building course that is integrated with all existing courses before all teaching staff (lecturers) become role models for students. As well as students realize that the value must be grown in themselves as self control to encourage each learning. Keywords: Character Building, Life Value Education